The influence of stoniness on the temperature of the arable horizon of alluvial meadow pebble soil during sprinkling under extreme conditions - Arsen N. Kurtnezirov; Anna E. Khadzhidi; Evgeny V. Kuznetsov (Мелиорация и гидротехника, 2025)
Purpose: to establish experimentally the influence of stoniness on temperature changes in the layers of the arable horizon of alluvial meadow pebble soil during sprinkling under extreme conditions. Materials and methods. The work was carried out in laboratory conditions on a large array of experimental material using computer programs. Methods of mathematical statistics were used in processing the experiments. Samples of alluvial meadow pebble soil with different stoniness were exposed to a light stream of 700 lux of a certain duration. The experimental results were obtained using calibrated electronic temperature sensors in the arable soil horizon. Results. It was found that the stoniness of alluvial meadow soils has a significant effect on the temperature regime of the arable horizon at extremely high temperatures during sprinkling. With the same light stream of 700 lx, which is observed at 14:00, alluvial meadow soil with different stoniness has different temperatures on the surface. With zero stoniness, the temperature is 49.5 °C; stoniness of 22.14 % – 65.1 °C; stoniness of 55.1 % – 86.1 °C, respectively. In the soil layers from 0 to 20 cm, when the soil surface is heated, the temperature increases to a maximum, then a smooth cooling is observed over 24 hours. Fourier's postulate is fulfilled in the soil. With stoniness of 55.1 %, the soil layers are most susceptible to the temperature influence. Conclusions. Experimental studies at extreme temperatures on the surface of the arable horizon of alluvial meadow pebble soil in mountain agricultural landscapes have shown that in order to create a favorable thermal regime during sprinkling, it is necessary to carry out measures to reduce the stoniness to 22.14 %. At the same time, in the arable soil horizon at a depth of 12 cm at a temperature of 29.5 °C, biochemical processes will be carried out that provide the necessary conditions for seed covering and the development of plants.